Hepatocyte dedifferentiation and extinction is accompanied by a block in the synthesis of mRNA coding for the transcription factor HNF1/LFB1. - Cereghini, S (1990)
The promoter proximal sequences of a group of liver-specific genes including that of albumin interact with the same hepato-specific factor named HNF1, LFB1, APF or HP1, a distant member of the homeoprotein family. A distinct protein, termed variant HNF1 (vHNF1), of lower mol. wt but displaying identical sequence specificity is found both in dedifferentiated variants and in an extinguished somatic hybrid that fail to express most or all of the tissue-specific traits, including albumin. We show here that HNF1 transcripts are present only in differentiated hepatoma cells. No transcripts are detected in dedifferentiated variants or in the extinguished cell hybrid, strongly suggesting that the vHNF1 protein is encoded by a distinct gene. Finally, HNF1 transcripts reappear in revertants to the hepatic phenotype. Run-on transcription analysis in isolated nuclei demonstrates that the expression of HNF1 in these cell lines is regulated primarily at the transcriptional level. Contrary to HNF1, the mRNAs coding for two other nuclear factors involved in albumin transcription, C/EBP and NF1, do not follow the distribution of albumin transcripts in these cell lines. These results indicate that extinction in somatic hybrids or loss of expression upon dedifferentiation of liver-specific genes possessing an HNF1 recognition site is caused, at least in part, by a block in HNF1 gene expression.